Nonlinear effect of wind velocity on mumps in Shenzhen, China, 2013–2016. (February 2020) - Zhou, Zhifeng; Mei, Shujiang; Chen, Jian; Li, Xueyun; Yin, Ling; Liang, Jing; Jiang, Lixin; Xu, Yucheng; Zhao, Menglan
Abstract: Objectives: Plenty of studies have shown that wind velocity has an influence on airborne diseases. There is, however, no consistent conclusion found on the relationship between wind velocity and mumps, and the regional heterogeneity has been largely neglected in previous studies. This study aims to explore the association between wind velocity and mumps in Shenzhen. Study design: Ecological study. Methods: Sixteen subdistricts with the highest incidence rates of mumps were selected from Shenzhen city, and the multilevel distributed lag-nonlinear model was conducted to explore the relationship between mumps cases and wind velocity via the dlnm and lme4 packages of the software R 3.4.3. Results: In Shenzhen, a total of 16, 997 mumps cases were reported between 2013 and 2016, and the means of daily rainfall, temperature, relative humidity, and 10 min wind velocity were 5.74 mm, 23.27 °C, 76.31% and 1.87 m/s, respectively. Obvious nonlinear correlation relationships of wind velocity and mumps risk were found, where a reverse-V curved shape was shown in the exposure dimension with the logRR value of mumps peaking at 2 m/s, and the type of nonlinear correlation varying with the levels of wind velocity in lag dimension with a peak at two lag weeks. Conclusions: The lag and nonlinear association between wind velocity and number of mumps cases were examined, while there was no statistically significant associations for other meteorological factors accounting for the regional heterogeneity. Results from this study indicated that public health administrators could strengthen health education in schools on ventilation management to prevent and control mumps outbreaks. Highlights: This study examined the associations between wind velocity and mumps. A multilevel distributed lag-nonlinear model was conducted. A multilevel distributed lag-nonlinear model was conducted to examine the association between wind velocity and mumps.